Exploring the validity of university‐based practicum tailored to develop expertise in addressing challenging behavior. Issue 4 (16th June 2022) - Lambert, Joseph M.; Paranczak, Jessica L.; Copeland, Bailey A.; Macdonald, M. Janey; Houchins‐Juarez, Nealetta J.
Abstract : In theory, the principles, processes, and concepts of applied behavior analysis are universally applicable. In practice, clinicians commit their lives to serving specific populations in specific settings for which specialization is needed. The purpose of this 6‐year retrospective consecutive case series was to describe and evaluate the quality and validity of a practicum experience tailored to develop specialized expertise in the assessment and treatment of challenging behavior for pre‐service practitioners enrolled in a department of a special education program.